2017
DOI: 10.1002/cne.24145
|View full text |Cite
|
Sign up to set email alerts
|

GABAergic innervation of the ciliary ganglion in macaque monkeys – A light and electron microscopic study

Abstract: The vertebrate ciliary ganglion (CG) is a relay station in the parasympathetic pathway activating the iris sphincter and ciliary muscle to mediate pupillary constriction and lens accommodation, respectively. While the postganglionic motoneurons in the CG are cholinergic, as are their inputs, there is evidence from avian studies that GABA may also be involved. Here, we used light and electron microscopic methods to examine the GABAergic innervation of the CG in Macaca fascicularis monkeys. Immunohistochemistry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“… 51 In this regard, the organization of the ciliary motoneurons is noteworthy. At the ultrastructural level, their somata are surrounded by a perisomatic neuropil that contains numerous synaptic contacts, 52 54 but they also emit a few dendrites. Both these characteristics were evident in the virus-labeled postganglionic motoneurons ( Figs.…”
Section: Discussionmentioning
confidence: 99%
“… 51 In this regard, the organization of the ciliary motoneurons is noteworthy. At the ultrastructural level, their somata are surrounded by a perisomatic neuropil that contains numerous synaptic contacts, 52 54 but they also emit a few dendrites. Both these characteristics were evident in the virus-labeled postganglionic motoneurons ( Figs.…”
Section: Discussionmentioning
confidence: 99%
“…The SCi connects to a downstream parasympathetic structure, the Edinger-Westphal (EW) nucleus, mainly via projections through the central mesencephalic reticular formation (40,41). The EW nucleus projects to the ciliary ganglion with excitatory and inhibitory connections (42) and can therefore produce constriction and dilation. Additionally, the EW nucleus receives projections from topographically organized the pretectal olivary nucleus (PON), which receives luminance signals directly from the retina (43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Figure 5A,B shows that this relaxation effect was replicated using pupil size, which was smaller for predictive versus reactive saccade trials. NE has been shown to have a neuromodulatory effect on the parasympathetic oculomotor complex via LC inputs to SC (Edwards et al, 1979) and SC's corresponding projection through Edinger-Westphal nucleus (Harting et al, 1980) to the ciliary ganglion, which can be both excitatory and inhibitory (Barnerssoi et al, 2017), providing a potential pathway for a decreased pupil size and thereby arousal for predictive saccades. This pupil effect is complementary to a previous fMRI study by Lee et al (2016) that demonstrated strong activation of the default mode network (DMN), a neural network that increases its metabolic activity during relaxation, when adults made predictive saccades in the metronome task.…”
Section: Pupil Size and Temporal Prediction Across Agementioning
confidence: 99%